2019
DOI: 10.2147/mder.s223794
|View full text |Cite
|
Sign up to set email alerts
|

<p>Electrical Analysis Of Normal And Diabetic Blood For Evaluation Of Aggregation And Coagulation Under Different Rheological Conditions</p>

Abstract: IntroductionErythrocyte aggregation and blood coagulation are of great interest and are still under investigation by many researchers. Erythrocytes have a direct effect on hemorheological properties. Real-time in vitro studies on blood coagulation and aggregation provide a chance to understand their mechanisms in normal and pathological conditions. Additionally, this method offers control over the physical and chemical conditions during the study.ObjectiveThe present study introduced a simple in vitro techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Among the limited research studies focused on diagnosing diabetes using blood conductivity, there are conflicting findings and lack of consensus. For example, researchers such as Abdalla et al [5] argue that diabetic blood is more conductive than normal blood, while others like Elblbesy [66] imply that diabetic blood is hyperaggregated compared to control blood, suggesting that the electrical conductivity of diabetic blood could be lower than normal blood. In this study, we also observed a complex relationship between blood Glc levels and its conductivity (Figure 2h,i).…”
Section: Discussionmentioning
confidence: 99%
“…Among the limited research studies focused on diagnosing diabetes using blood conductivity, there are conflicting findings and lack of consensus. For example, researchers such as Abdalla et al [5] argue that diabetic blood is more conductive than normal blood, while others like Elblbesy [66] imply that diabetic blood is hyperaggregated compared to control blood, suggesting that the electrical conductivity of diabetic blood could be lower than normal blood. In this study, we also observed a complex relationship between blood Glc levels and its conductivity (Figure 2h,i).…”
Section: Discussionmentioning
confidence: 99%